Комбiнацiйне розсiювання свiтла в надґратках з Ge квантовими точками - Romanyuk, Yu. A.; Yaremko, A. M.; Dzhagan, V. M.; Yukhymchuk, V. O. (Publishing house "Academperiodika", 2019)
The studies of the Raman scattering in superlattices with layers of Ge quantum dots (QDs) are carried out. A theoretical model describing the experimental spectra with regard for the real crystal structures of both the QD and the surrounding matrix, as well as the phonon-phonon interaction in the matrix and in the QDs, is proposed. The intensities of Raman spectra are calculated with the use of the secondary quantization procedure and Green’s functions. The results obtained show that the crystal structure of the superlattice composed of alternating silicon layers and layers with Ge quantum dots can be described as a mixed crystal consisting of a matrix with a certain distribution of “impurities” (“Ge-molecules”). A qualitative correlation between the theoretically calculated and experimentally measured positions and intensities of bands in the Raman spectra of QD superlattices is demonstrated, and the doublet character of the bands is explained.